The dual-suppression of peak electric field in AlGaN/GaN HEMT with sandwich structure. (April 2021) - Zou, Hao; Yang, Lin-An; Ma, Xiao-Hua; Hao, Yue
Abstract: To improve the power and RF performance of the high electron mobility transistors (HEMTs) based on AlGaN/GaN heterostructure junction, in this paper, a sandwich structure consisting of gate field plate, SiN passivation layer, and notch structure is proposed. The notch structure at the AlGaN barrier layer between the gate and drain is formed by the Inductively Coupled Plasma etching system (ICP), and the notch has a depth of 15 nm. The dual-suppression of the peak electric field contributes to the breakdown voltage of 91 V, which is a 152.8% improvement compared with the conventional HEMT. The decrease of C gd due to increase of distance between the gate electrode and the lower surface of the depletion layer contributes to the cut-off frequency of 24.1 GHz, which is an 8% improvement. Thus, this composite-structure HEMT has a JFOM of 2.2 THz V, it is an 84.6% improvement compared with the conventional gate field plate HEMT. A well suppression of current collapse is also achieved. It has potential in high power and RF applications. Highlights: The Sandwich structure manufacturing process is compatible with the conventional process for AlGaN/GaN HEMTs. The Sandwich structure has a good suppression on the peak electric field, and it can decrease the capacitance between the gate and drain. The Sandwich structure not only improves the breakdown characteristic but also improves the cut-off frequency characteristics. The manufacturing process of the notch structure at AlGaN barrier layer does not cause the surface damage.